Immunotherapy targeting isoDGR-protein damage extends lifespan in a mouse model of protein deamidation - Kalailingam, Pazhanichamy (2024)
Aging results from the accumulation of molecular damage that impairs normal biochemical processes. We previously reported that age-linked damage to amino acid sequence NGR (Asn-Gly-Arg) results in "gain-of-function" conformational switching to isoDGR (isoAsp-Gly-Arg). This integrin-binding motif activates leukocytes and promotes chronic inflammation, which are characteristic features of age-linked cardiovascular disorders. We now report that anti-isoDGR immunotherapy mitigates lifespan reduction of Pcmt1-/- mouse. We observed extensive accumulation of isoDGR and inflammatory cytokine expression in multiple tissues from Pcmt1-/- and naturally aged WT animals, which could also be induced via injection of isoDGR-modified plasma proteins or synthetic peptides into young WT animals. However, weekly injection of anti-isoDGR mAb (1 mg/kg) was sufficient to significantly reduce isoDGR-protein levels in body tissues, decreased pro-inflammatory cytokine concentrations in blood plasma, improved cognition/coordination metrics, and extended the average lifespan of Pcmt1-/- mice. Mechanistically, isoDGR-mAb mediated immune clearance of damaged isoDGR-proteins via antibody-dependent cellular phagocytosis (ADCP). These results indicate that immunotherapy targeting age-linked protein damage may represent an effective intervention strategy in a range of human degenerative disorders.